2013
DOI: 10.2205/2013es000531
|View full text |Cite
|
Sign up to set email alerts
|

Fractal aggregates in the atmosphere

Abstract: In this paper we consider the properties of fractal aggregates suspended in the Earth atmosphere. Fractal aggregates (FA) are now well established to appear in numerous natural and anthropogenic processes. Their role in the atmosphere is immense, for FA possess anomalous physico-chemical, mechanical and optical properties making them extremely effective atmospheric agents. The main goal of this paper is to overview the mechanisms of FA formation, their properties, to discuss sources and sinks of the atmospheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The attempts of modelling this important and still enigmatic process also appeared rather long ago. Here we avoid the long history of this problem and cite only the last models appeared in the XXI century: [Barret and Clement, 1991;Clement and Ford, 1999;Clement et al, 2006;Adams et al, 2002;Korhonen et al, 2003;Lehtinen and Kulmala, 2003;Easter et al, 2004;Anttila et al, 2004;Korhonen et al, 2004;Grini et al, 2005;Lushnikov et al, 2013aLushnikov et al, , 2013bLushnikov et al, 2014;Elperin et al, 2013;Stolzenberg et al, 2005;Spracklen et al, 2006]. The extensive earlier citations can be found in the above listed papers.…”
Section: Nucleation Bursts In the Atmospherementioning
confidence: 99%
“…The attempts of modelling this important and still enigmatic process also appeared rather long ago. Here we avoid the long history of this problem and cite only the last models appeared in the XXI century: [Barret and Clement, 1991;Clement and Ford, 1999;Clement et al, 2006;Adams et al, 2002;Korhonen et al, 2003;Lehtinen and Kulmala, 2003;Easter et al, 2004;Anttila et al, 2004;Korhonen et al, 2004;Grini et al, 2005;Lushnikov et al, 2013aLushnikov et al, , 2013bLushnikov et al, 2014;Elperin et al, 2013;Stolzenberg et al, 2005;Spracklen et al, 2006]. The extensive earlier citations can be found in the above listed papers.…”
Section: Nucleation Bursts In the Atmospherementioning
confidence: 99%
“…The importance of the morphology of dust particles on the early Earth's radiation environment is studied in [16]. Fractal structures of particulate matter have been analyzed in the context of the global threat to public health [17][18][19], and in relation to the warming effects in the Earth's atmosphere in [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental techniques used to investigate irregularly shaped structures included light scattering and transmission electron microscopy (TEM) (Lin et al 1990;Puri et al 1993;Wentzel et al 2003). Researchers have found that atmospheric agglomerates (for, e.g., soot and fly ash) grow mainly by cluster-cluster coagulation and reveal self-similarity; hence, they can be called fractal-like structures that follow the rules of power law scaling (Lee et al 2003;Zhu et al 2005;Lushnikov et al 2013). Thus, the introduction of fractal geometry enabled a convenient and effective mathematical description of structures like particulate matter agglomerates and provided a way to parameterize aerosol properties.…”
Section: Introductionmentioning
confidence: 99%